2018
DOI: 10.1038/s41386-018-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

D1 receptor hypersensitivity in mice with low striatal D2 receptors facilitates select cocaine behaviors

Abstract: Vulnerability for cocaine abuse in humans is associated with low dopamine D2 receptor (D2R) availability in the striatum. The mechanisms driving this vulnerability are poorly understood. In this study, we found that downregulating D2R expression selectively in striatal indirect-pathway neurons triggers a multitude of changes in D1 receptor (D1R)-expressing direct-pathway neurons, which comprise the other main subpopulation of striatal projection neurons. These changes include a leftward shift in the dose-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…We propose that striatal D1R hypersensitivity is the substrate linking these vulnerability factors. In a recent publication, we showed D1R hypersensitivity under conditions of low striatal D2Rs in medium spiny neurons (Dobbs et al, 2019). Here, we demonstrate that this upregulation in D1Rs is functionally relevant, with D1Rs driving ethanol stimulation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We propose that striatal D1R hypersensitivity is the substrate linking these vulnerability factors. In a recent publication, we showed D1R hypersensitivity under conditions of low striatal D2Rs in medium spiny neurons (Dobbs et al, 2019). Here, we demonstrate that this upregulation in D1Rs is functionally relevant, with D1Rs driving ethanol stimulation.…”
Section: Discussionmentioning
confidence: 86%
“…We hypothesized that acute ethanol exposure would also activate D1R activity and lead to protein kinase A (PKA)-dependent phosphorylation of downstream targets, such as pGLUA1 at serine-845. Furthermore, we predicted that iMSN-Drd2KO mice would display enhanced activation of targets downstream of D1R based on our recent findings that mice lacking medium spiny neuron D2Rs display D1R hypersensitivity at both the cellular/signaling and behavioral levels (Dobbs et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings support the simultaneous requirement of activity of both striatal projection pathways (D1-MSNs and D2-MSNs) in the dorsal striatum for proper action initiation and for proper continuation of performance after initiation [64,65]. Supporting these findings, an imbalance in the activity of D1-MSNs and D2-MSNs is hypothesized to contribute to the development and persistence of addiction [66,67]. For example, a few studies have revealed opposing roles of D1Rs and D2Rs in the dorsal striatum in cocaine taking and seeking behaviors [67,68,69].…”
Section: Discussionmentioning
confidence: 66%
“…Supporting these findings, an imbalance in the activity of D1-MSNs and D2-MSNs is hypothesized to contribute to the development and persistence of addiction [66,67]. For example, a few studies have revealed opposing roles of D1Rs and D2Rs in the dorsal striatum in cocaine taking and seeking behaviors [67,68,69]. A recent study indicated that downregulation of striatal D2Rs triggers D1R hypersensitivity to facilitate greater cocaine taking behavior [67].…”
Section: Discussionmentioning
confidence: 99%